The Importance of Including Culture in EFL Teaching - Purba, Hemat (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2011)
Language and culture are two inseparable entities. Therefore, language learning is at once a cultural learning. One’s mastery of the linguistic elements alone does not guarantee he will be able to communicate through a language. Mastering the cultural element is a must. This paper discusses various research findings and opinions on the integration of culture into the teaching of foreign language teaching. The discussion aimed to highlight the foundation, the existence, impact, and technical integration of cultural elements into the teaching of English as a foreign language.